Epidemiology of Lung Cancer in Iran: Sex Difference and Geographical Distribution - Salman Khazaei; Kamyar Mansori; Mokhtar Soheylizad; Behzad Gholamaliee; Fatemeh Khosravi Shadmani; Zaher Khazaei; Erfan Ayubi (Middle East Journal of Cancer, 2017)
Background: Lung cancer is one of the most common cancers and most frequent cause of cancer-related death worldwide. In Iran, this cancer ranks second in cancerrelated deaths for men and third for women. The aim of this study is to discover the geographic distribution of the age-standardized incidence rate for lung cancer in both genders in Iran. Methods: This ecological study used re-analysis medical records aggregated to provinces from the National Registry of Cancer and Disease Control and Prevention Report of the Ministry of Health and Medical Education for lung cancer in 2008. For each province, we calculated the average annual age-standardized incidence rate. Results:Our study showed that squamous cell carcinoma and adenocarcinoma were the most common histological types of lung cancer in males (28.6%) and females (28.8%). The central and southern Iranian provinces had the highest age-standardized incidence rates for lung cancer. The highest age-standardized incidence rates in both genders related to the 80-84 year age group for both males (131.51) and females (38.82). Conclusion: The central and southern Iranian provinces are lung cancer hot zones. Thus, implementation of prevention programs and increased access to screening services should be considered.